2019
DOI: 10.1097/prs.0000000000006292
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Visual Perception of Female Breast Aesthetics and Symmetry: An Eye-Tracking Study

Abstract: Background: Because of its subjective character, the term “breast attractiveness” is poorly defined and thus its reliable standardized assessment can be particularly challenging. Because of objective analysis of the observer’s gaze pattern, eye-tracking technology may provide a better insight into the visual perception of breast aesthetics and symmetry. Methods: One hundred observers, 50 women and 50 men, assessed the aesthetics and symmetry of eight ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…The mean areola diameter (MW AD) was the only body measurement in our work that had a signi cant in uence on the long-term outcome. With this nding our study supports the results of Pietruski et al [43], who recently showed in their eye tracking study that the nipple-areola complex is one of two key focus areas of the female breast.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…The mean areola diameter (MW AD) was the only body measurement in our work that had a signi cant in uence on the long-term outcome. With this nding our study supports the results of Pietruski et al [43], who recently showed in their eye tracking study that the nipple-areola complex is one of two key focus areas of the female breast.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…The mean areolar diameter (MW AD) was the only body measurement in our work that had a significant influence on the long-term outcome. With this finding, our study supports the results of Pietruski et al [ 43 ], who recently demonstrated in their eye-tracking study that the nipple-areola complex is one of two key focus areas of the female breast.…”
Section: Discussionsupporting
confidence: 93%
“…The five experimental design studies were the same five studies that demonstrate misogyny ( Table 4 ). These five studies were conducted in the United Kingdom ( n = 2), 40 , 41 Poland ( n = 2), 42 , 43 and Italy ( n = 1). 21 Results are presented in Tables 3 and 4 .…”
Section: Resultsmentioning
confidence: 99%
“… 21 , 40 , 42 Pietruski et al conducted an analysis of visual tracking of the aesthetic of breasts, however, also stated their method is potentially flawed in that there is limited evidence as to how visual patterns translate to assessment of attractiveness. 43 …”
Section: Resultsmentioning
confidence: 99%